Socio-economic study of a Fermented Drink « Dèguè » made with Milk and Cereales in Benin - TCHEKESSI, C. K. Célestin; BANON, Jultesse; SENI, Isac; GANDEHO, Justin G.; AGBANGLA, CLÉMENT; AZOKPOTA, Paulin; ANGELOV, Angel; BOKOSSA YAOU, Innocent Padonou (My University, 2014)
Dèguè is a fermented drink made from a mixture of dumplings cereals steamed and fermented milk. The present study aims at evaluating the production technologies and the marketing of dèguè in Benin. For this, a socio-economic survey was conducted in the municipalities of greater production and consumption of dèguè in the south, the centre and the north of Benin. The results obtained show that dèguè is of Fulani origin and came mainly from Benin and many other countries of West Africa. All producers (100%) use as raw materials millet and milk powder bought in local markets in Benin. In addition, 30.10% use more millet, couscous of wheat to make a second variety of dèguè called dèguè-couscous. Statistic analysis revealed that, dèguè producers use almost the same technology in Benin. The production of this drink is based on the traditional technology that most producers have inherited from their parents. Today, dèguè is sold in schools, universities, markets and along the public roads. It is consumed by people of all ages. According to the consumers dèguè is rich in vitamin, it gives energy and it is as refreshing. Dèguè production is a profitable business that provides a significant daily gain.
Keywords: cereals; milk; dèguè; socio-economy.